2016
DOI: 10.1177/0894318416630090
|View full text |Cite
|
Sign up to set email alerts
|

Building a Middle-Range Theory of Adaptive Spirituality

Abstract: The purpose of this article is to describe a Roy adaptation model based-research abstraction, the findings of which were synthesized into a middle-range theory (MRT) of adaptive spirituality. The published literature yielded 21 empirical studies that investigated religion/spirituality. Quantitative results supported the influence of spirituality on quality of life, psychosocial adjustment, well-being, adaptive coping, and the self-concept mode. Qualitative findings showed the importance of spiritual expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The presentation regarding this last stage of life is offered by an experienced palliative care nurse. This focus is consistent with previous work with the RAM on adaptation in death and dying (Dobratz, 2004(Dobratz, , 2011(Dobratz, , 2016.…”
Section: Focal Stimulisupporting
confidence: 90%
“…The presentation regarding this last stage of life is offered by an experienced palliative care nurse. This focus is consistent with previous work with the RAM on adaptation in death and dying (Dobratz, 2004(Dobratz, , 2011(Dobratz, , 2016.…”
Section: Focal Stimulisupporting
confidence: 90%
“…While the individual-difference factors above refer to relatively consistent and enduring dispositional differences, we note that values attitudes, and beliefs (which are characterized as being more changeable over time and situations) can also be related to positive coping outcomes. For example, research highlights the crucial role that differences in beliefs and values around spirituality can play in predicting positive health and psychological outcomes (Abraído-Lanza et al, 2004; Andersen et al, 2014; Bai et al, 2015; Bergman et al, 2011; Bovero et al, 2016; Dobratz, 2016; Kharame et al, 2014; Weinert et al, 2008; Whitford and Olver, 2012; Whitford et al, 2008; Wijesinghe and Parshall, 2016). For example, spirituality was an important predictor of quality of life for Italian patients with advanced cancer (Bovero et al, 2016) and was highly associated with adopting a “fighting spirit” in Australian patients with early stage cancer (Whitford and Olver, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the self-initiated and knowing-based coping, the items of CAPS-SF-C were self-centered such as in the words "in my favor." Spirituality was framed within the self-concept mode and suggested that a person existed for a purpose and created value and meaning of life (Dobratz, 2016). Seeking supports from healthcare professionals, family/friends, and peers, which is common in dealing with chronic diseases, is related to others' resources and the expansion of an individual's inner strength during adaptation process.…”
Section: Discussionmentioning
confidence: 99%